2019
DOI: 10.1111/1365-2478.12878
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale phase inversion for 3D ocean‐bottom cable data

Abstract: We invert three‐dimensional seismic data by a multiscale phase inversion scheme, a modified version of full waveform inversion, which applies higher order integrations to the input signal to produce low‐boost signals. These low‐boost signals are used as the input data for the early iterations, and lower order integrations are computed at the later iterations. The advantages of multiscale phase inversion are that it (1) is less dependent on the initial model compared to full waveform inversion, (2) is less sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We found that it is not necessary to include all 25 channels in the input due to the redundancy among seismic data records, so our input only contains 8 channels (6,7,8,11,13,16,17,18). See Figure 11 for an explanation of these serial numbers.…”
Section: ) Training Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that it is not necessary to include all 25 channels in the input due to the redundancy among seismic data records, so our input only contains 8 channels (6,7,8,11,13,16,17,18). See Figure 11 for an explanation of these serial numbers.…”
Section: ) Training Configurationsmentioning
confidence: 99%
“…Key ingredients of FWI are an efficient forward-modeling engine and a local differential approach to calculate the gradient and the Hessian operators [3]. As 3D surveys become widely implemented, 3D FWI are required to solve complex geological cases [4], [5], [6]. However, both the computational cost of forward-modeling and the gradient calculation are much higher in the 3D cases than the 2D cases [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the multi-scale inversion strategy is also applicable to the GPR domain [24]. To solve the problems existing in the traditional FWI inversion process, a series of waveform inversion methods based on special objective functions are proposed [25][26][27][28][29][30][31]. Subsequently, the partial information waveform inversion method based on special objective function was successfully developed in the field of GPR [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they replaced the magnitudes of the predicted spectra with those of the recorded spectra. This method has been successfully applied to crosswell data (Sun and Schuster, 1993) and surface reflection seismic data (Fu et al, 2017(Fu et al, , 2020Feng et al, 2019a). In this paper, we extend the multiscale phase inversion methodology to data recorded over an anisotropic medium.…”
Section: Introductionmentioning
confidence: 99%